Design of Cyberwar Laboratory Exercises to Implement Common Security Attacks against IEEE 802.11 Wireless Networks. (26th December 2010) - Malekzadeh, Mina; Abdul Ghani, Abdul Azim; Subramaniam, Shamala
Abstract : In wireless network communications, radio waves travel through free space; hence, the information reaches any receiving point with appropriate radio receivers. This aspect makes the wireless networks vulnerable to various types of attacks. A true understanding of these attacks provides better ability to defend the network against the attacks, thus eliminating potential threats from the wireless systems. This work presents a series of cyberwar laboratory exercises that are designed for IEEE 802.11 wireless networks security courses. The exercises expose different aspects of violations in security such as confidentiality, privacy, availability, and integrity. The types of attacks include traffic analysis, rogue access point, MAC filtering, replay, man-in-the-middle, and denial of service attacks. For each exercise, the materials are presented as open-source tools along with descriptions of the respective methods, procedures, and penetration techniques.